Food in correctional facilities: A scoping review - Smoyer, Amy B. (Appetite, 2019)
In the last 20 years, there has been an exponential increase in research about food in prison. Given this growing interest, it is appropriate to take stock of the field by mapping and synthesizing existing knowledge in order to identify gaps in knowledge and make recommendations for future research. Specifically, the purpose of this scoping review is to understand the experiences of incarcerated people with food in order to inform interventions that will promote positive outcomes for justice-involved individuals and correctional facilities. This review identified 38 peer-reviewed research articles about food in correctional facilities. This sample included qualitative (n = 28) and quantitative (n = 10) research that explored the both the pragmatic and symbolic dimensions of food in these settings. Taken together, this body of research provides a rich description of prison food practices and the implications of these practices on medical, psychological, and sociological outcomes. Moving forward, collaboration between academics, incarcerated people, and correctional practitioners is encouraged in order to develop programs that use this research to improve individual and intuitional outcomes. In addition, while emerging research has begun to develop knowledge about prison food in developing countries, the literature focuses primarily on the US, Canada and Western Europe and there is a need to expand the geographic scope of this inquiry.
19 citations (Crossref) [2023-10-31] Place: England Smoyer, Amy B. Department of Social Work, Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, USA. Electronic address: smoyera1@southernct.edu.
Keywords: *Food Services; *Prisons; Canada; Consumer Behavior; Europe; Food Services; Humans; Nutritive Value; Prisons; United States; Western Europe; adult; article; catering service; clinical article; consumer attitude; dept.swk; developing country; female; human; justice; male; nutritional value; peer-reviewed; physician; prison

“It's the black girls that have the most”: foodways narratives and the construction of race in a women's prison - Smoyer, Amy B (Food and Foodways, 2015)
Prison foodways narratives can expand knowledge about cultural beliefs and perceptions of correctional systems. This exploratory analysis, based in qualitative interview data, seeks to initiate dialogue about the ways in which formerly incarcerated women in the US deploy racialized food narratives when describing the acquisition, preparation, and consumption of prison food. The participants’ food narratives construct prison as a non-white space that is better matched for African-American and Latina women, reinforcing and enacting larger cultural notions about incarceration. This opening analysis calls for more research and deliberation about how prison foodways narratives contribute to understandings about and perceptions of correctional systems and incarcerated people. © 2015, Taylor & Francis Group, LLC.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-302-356-756-556 tex.type: [object Object]
Keywords: dept.swk

Making fatty girl cakes: food and resistance in a women's prison - Smoyer, Amy B. (The Prison Journal, 2016)
This article builds on existing knowledge of inmate resistance by analyzing formerly incarcerated women's narratives about prison food. Participants described trying to secure extra cafeteria portions, hoarding food, smuggling and stealing food, and cooking and eating in the cellsall to resist prison power and gain some control over their lives by managing what, how, when, and with whom they ate. These data shed light on prison life and suggest changes to food policy to curb inmate resistance and bolster the rehabilitative potential of correctional facilities.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/095-837-797-757-693 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk; food; prisoners; resistance; women

Feeding relationships: foodways and social networks in a women’s prison - Smoyer, Amy B. (Affilia, 2014)
Research has demonstrated the importance of supportive relationships and social networks to prisoners’ psychosocial outcomes, especially for women. Understandin...
25 citations (Crossref) [2023-10-31] Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: dept.swk; peer-reviewed

Hungry on the inside: Prison food as concrete and symbolic punishment in a women’s prison - Smoyer, Amy B; Lopes, Giza (Punishment & Society, 2017)
Women’s perceptions of the prison experience and the punishing dimensions of their confinement are under-examined. To expand knowledge in this area, Sexton’s theory of penal consciousness is used to analyze formerly incarcerated women’s narratives about prison food. This analysis builds understanding about the lived experience of incarceration by explicating one dimension of prisoners’ understandings and perceptions of punishment. Women’s narratives describe both concrete and symbolic punishments associated with food. Participants spoke about poorly designed, sloppy food systems that left them feeling uncared for, ignored, frustrated, and humiliated. Women articulate experiences of hunger that reflect both a deprivation of adequate food and a rationing of humane attentions. These punishing perceptions may inhibit the efforts of social service and health providers to engage incarcerated and formerly incarcerated women in care. In contrast, exceptional participant narratives about positive, non-punishing food experiences suggest that ameliorated food systems could improve the lived experience of incarceration and promote the engagement in services that is needed to improve the outcomes of incarcerated and formerly incarcerated women.
54 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000395402500006, lens.org/015-306-581-234-40X tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk; food; prison; punishment; women

Dealing food: Female drug users’ narratives about food in a prison place and implications for their health - Smoyer, Amy B.; Blankenship, Kim M. (International Journal of Drug Policy, 2014)
18 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Food systems in correctional settings: a literature review and case study - Smoyer, Amy B.; Kjær Minke, Linda (World Health Organization. Regional Office for Europe, 2015)
Food is a central component of life in correctional institutions and plays a critical role in the physical and mental health of incarcerated people and the construction of prisoners’ identities and relationships. An understanding of the role of food in correctional settings and effective management of food systems may improve outcomes for incarcerated people and help correctional administrators to maximize the health and safety of individuals in these institutions. This report summarizes existing research about food systems in correctional settings and provides examples of food programmes in prison and remand facilities, including a case study of food-related innovation in the Danish correctional system. Specific conclusions are offered for policy-makers, administrators of correctional institutions and prison food services professionals,and ideas for future research are proposed.
Accepted: 2019-08-13T14:39:22Z
Keywords: dept.swk

Prison food in Denmark: Normal responsibility or ethnocentric imaginations? - Minke, Linda Kjær; Smoyer, Amy B. (Scandinavian penal history, culture and prison practice - Embraced by the welfare state?, 2017)
This book draws on historical and cross-disciplinary studies to critically examine penal practices in Scandinavia. The Nordic countries are often hailed by international observers as ‘model societies’, with egalitarian welfare policies, low rates of poverty, humane social policies and human rights...
Citation Key Alias: lens.org/077-884-123-268-809, minkePrisonFoodDenmark2017a
Keywords: dept.swk

Setting the stage: creating study sites that promote the safety and dignity of research participants - Smoyer, Amy B.; Rosenberg, Alana; Blankenship, Kim M. (Social Work Research, 2014)
The U.S. Department of Health and Human Services' (HHS) Code of Federal Regulations regarding Protection of Human Subjects (45 C.F.R. part 46) provides guidance
1 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Stigma, housing and identity after prison. - Keene, Danya E; Smoyer, Amy B; Blankenship, Kim M (The Sociological review, 2018)
Existing research suggests that individuals who are released from prison face considerable challenges in obtaining access to safe, stable, and affordable places to live and call home. This article draws on repeated qualitative interviews (conducted every 6 months over a period of 3 years) with 44 formerly incarcerated individuals, to understand how these individuals experience the search for a home after their prison release. The interviews show that the quest for a home is central to participants' reintegration projects as they seek to establish themselves as 'decent' and economically self-sufficient citizens, and shed stigmatized identities associated with incarceration, poverty, homelessness, and place. Interviews also suggest that their quest for a home is an arduous one as they encounter numerous barriers to housing arising from both structural and interpersonal forms of incarceration stigma. Somewhat paradoxically, the challenges that they face in accessing housing seem to hinder their ability to shed the stigmatized identities associated with their incarceration. Ultimately, the narratives presented here show how stigma can restrict access to a valuable material and symbolic resource (housing), resulting in ongoing stigmatization, and contributing to the enduring and discrediting mark of incarceration. In this way, the study illustrates how stigma that is enacted by both individuals and the state, that is embodied in place, and that is internalized and managed by stigmatized individuals themselves, can work to reproduce power and serve as justification for inequality.
54 citations (Crossref) [2023-10-31] Place: England Keene, Danya E. Yale School of Public Health, USA. Smoyer, Amy B. Southern Connecticut State University, USA. Blankenship, Kim M. American University, Washington, DC, USA.
Keywords: Housing; Incarceration; Spatial stigma; dept.swk; peer-reviewed

Older adults’ lived experience of incarceration - Smoyer, Amy B.; Madera, Johanna Elumn; Blankenship, Kim M. (Journal of Offender Rehabilitation, 2019)
This qualitative analysis explores older adults’ lived experiences of incarceration. As part of a larger mixed-methods longitudinal study, 23 older adults were interviewed about their prison and reentry experiences. Findings describe experiences of loss, lack of medical attention, abuse by staff and other inmates, and the uncertainties and danger of prison life. After release, participants reported experiencing anxiety and stress related to their prison experiences. While participants reported that the ability to manage prison life deteriorated with age, some benefits of their senior status were also described. Maturity may allow older prisoners to remove themselves from volatile situations. Participants described experiences of rest and recovery, reflecting coping mechanism and resilience that could improve psychosocial outcomes during and after prison. This descriptive analysis centers the voices of older prisoners and informs interventions to support this vulnerable community.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-126-745-669-828, pop00096 tex.type: [object Object]
Keywords: Prison; dept.swk; incarceration; older people; peer-reviewed; qualitative; reentry